(untitled) (Research, Society and Development, 2024)
Leprosy, or Hansen’s disease, is a chronic granulomatous disease caused by the bacterium Mycobacterium leprae, primarily affecting the peripheral nervous system, skin, and reticuloendothelial system. It predominantly affects individuals living in poor communities in underdeveloped and developing tropical countries, and is considered a neglected tropical disease. Brazil has been responsible for the second highest number of cases, following only India. Understanding the epidemiological and spatial patterns of leprosy and their relationship with socioeconomic factors is essential for the effective control of this disease. For this reason, this study aims to evaluate the spatial and spatiotemporal patterns of leprosy cases in the Northeast region of Brazil from 2001 to 2020. Through an ecological study based on spatial analysis techniques using secondary data from reported leprosy cases in the Northeast state, the region recorded 29,817 new cases of the disease over the nineteen years from 2001 to 2020. Although the trend of new leprosy cases has shown a decline, many municipalities are still classified as hyperendemic. In light of these results, we recommend implementing health education in areas considered hyperendemic, with the goal of raising awareness among the population about the importance of early treatment, thereby improving early diagnosis and treatment of the disease and achieving control over it.